DIGITALISASI DAN REPOSITORI DOKUMEN PADA DESA KARANGDUREN KEC.PAKISAJI, KAB.MALANG UNTUK MENINGKATKAN PELAYANAN MASYARAKAT - Yuri Arianto; Atiqah Nurul Asri; Mungki Astiningrum; Yoppy Yunhasnawa; Toga Aldila Cinderatama; Yan Watequlis Syaifudin (Jurnal Pengabdian kepada Masyarakat, 2023)
Village administration's core lies in directly addressing community needs. However, Karangduren village in Kab. Malang faces challenges due to its reliance on traditional paper-based governance. This leads to recurring difficulties in managing documents. To tackle these issues, the proposed Community Service (PPM) initiative, "Enhancing Village Governance Services in Karangduren Kec. Pakisaji, Kab. Malang through Digitalization and Document Repositories," aims to modernize processes.The initiative seeks to transition to digital methods for streamlined data management. The objective is to establish a comprehensive digital document repository system, simplifying the storage, access, and retrieval of crucial records. By adopting digitization, Karangduren Village aligns with the trend of incorporating information systems into governance practices.The project entails collaboration between the PPM team and students, who will conduct surveys, analyze system requirements, and implement the digital document repository framework within the village government. This effort corresponds with the 2021-2025 PPM Strategic Plan and Focus of the Malang State Polytechnic, emphasizing the revitalization of social and tourism infrastructure through technology, policy models, and research-based social engineering.Embedded in the village development program, this PPM activity contributes to capacity building and knowledge dissemination, reinforcing the partner village through innovative technological solutions.